Extrusion 3D printing of keratin protein hydrogels free of exogenous chemical agents. (1st September 2022) - Brodin, Erik; Boehmer, Melanie; Prentice, Alexandra; Neff, Emily; McCoy, Kathleen; Mueller, Jens; Saul, Justin; Sparks, Jessica L
Abstract: Keratins are a class of intermediate filament proteins that can be obtained from numerous sources including human hair. Materials fabricated from keratins offer desirable characteristics as scaffolds for tissue engineering, including intrinsic cell adhesion sequences and tunable degradation kinetics. The capacity to create 3D printed constructs from keratin-based bio-inks generates unique opportunities for spatial control of scaffold physicochemical properties to direct scaffold functions in ways not readily achieved through other means. The aim of this study was to leverage the controllable rheological properties of keratin hydrogels to create a strategy for extrusion 3D printing of keratin bio-inks without the use of exogenous rheological modifiers, crosslinking agents, or photocurable resins. The rheological properties of keratin hydrogels were tuned by varying two parameters: (a) the ratio of keratose (obtained by oxidative extraction of keratin) to kerateine (obtained by reductive extraction of keratin); and (b) the weight percentage of total keratin protein in the gel. A computational model of the dispensing nozzle for a commercially available extrusion 3D printer was developed to calculate the needed pneumatic printing pressures based on the known rheological properties of the gels. Keratin hydrogel constructs, of varying keratose/kerateine ratios and total keratin weight percentages, were 3D printed in cylindrical geometries via extrusion 3D printing. Rheology and degradation studies showed that gels with greater relative kerateine content exhibited greater flow resistance and slower degradation kinetics when submerged in phosphate buffered saline solution at 37 °C, owing to the presence of cysteine residues in kerateine and the capability of forming disulfide bonds. Total keratin weight percentage was found to influence gel yield stress, with possible implications for tuning filament fidelity. Findings from this work support the use of keratose/kerateine ratio and total keratin weight percentage as handles for modulating rheological characteristics of keratin hydrogels to enhance printability and control scaffold properties.